Rational Use Of Water – A Guarantee Of Preservation Of The Future (Texas Journal of Multidisciplinary Studies, 2022)
The world, whose goal is now developing, says that the increasing demand for Water Resources has become an important problem due to the increasing demand for human hormones, and thus the preservation of Water Resources has become an important problem. In the coming years, the strategy plans of the countries of Central Asia in the age of Water Resources and what their outcome could be, have been explained in detail.